Structural masonry and earthquakes - Lourenço, Paulo B. (2006)
[Excerpt] In the past and recent history there are several testimo-nies of the devastating effects of earthquakes. Given its nat-ure it is very likely that earthquakes with large destructivepotential occur in the future, in locations where the historicseismology has recorded past earthquakes of strong magni-tude. The responsibility of the authorities, researchers,designers and contractors is to reduce seismic vulnerability,reducing economical and human life losses. This appliesboth to new and existing buildings, most of which are madeof masonry walls.After the strong earthquakes of beginning of the 20thcentury and the widespread of reinforced concrete and steelas building materials, the feeling that masonry cannot with-stand seismic loads has been growing in developing coun-tries. This perception is incorrect and against sustainabledevelopment. It hinders the development of a cost-compet-itive building technology and the adequate conservation ofthe built heritage. [...]